The Prevalence, Popular Trends, and Associated and Predictive Factors of Non-Obese Fatty Liver Disease - Deng, Jiang; Zhang, Yonghong; Bu, Limei; Shi, Haitao; Tang, Hailing; Wang, Shenhao; Wang, Qian; Dang, Shuangsuo; Li, Ming; Han, Zhiyi; Lu, Xiaolan (Frontiers in Endocrinology, 2021)
Background and Aims There are few studies on non-obese fatty liver disease, the aims of this study was to analyze its prevalence, popular trends, and associated and predictive factors, so as to provide reference for its prevention and treatment. Methods Individuals with complete data of body mass index, sex, age, and abdominal ultrasound in Karamay Central Hospital from 2009 to 2016 were selected to analyze the prevalence and popular trends of non-obese fatty liver disease (body mass index <24 kg/m2), and associated and predictive factors. Results Between 2009 and 2016, a total of 191,555 medical check-ups were included. The prevalence of non-obese fatty liver disease increased from 1.9% to 5.1% among general medical examinants (P<0.001), increased from 4.6% to 11.7% in non-obese individuals (P<0.001). Compared with the non-obese control group, the levels of age, body mass index, blood pressure, fasting blood glucose, triglycerides, total cholesterol and uric acid in the non-obese fatty liver group were higher (P<0. 05). Even among non-obese subjects, elevated body mass index was associated with a 0.63-fold increased risk for non-obese fatty liver disease (P<0.001, odds ratio=1.63, 95% confidence interval 1.54-1.72) for every one-unit increase in body mass index. The most common abnormal indicator of non-obese fatty liver disease was elevated triglycerides (44.2%), which was also the best predictor of non-obese fatty liver disease (area under the curve =0.795) in non-obese physical examinators. Conclusions The prevalence of non-obese fatty liver disease was high and increasing rapidly in Karamay. Triglycerides is the best predictor of non-obese fatty liver in non-obese physical examinators.